A Periodontite como fator de exposição e desfecho na associação com condições e doenças sistêmicas - Miranda, Samilly Silva (2016)
Periodontitis is a multifactorial disease, bacterial primary etiology, but presents external factors that influence its development. It has also been considered exposure to systemic diseases, such as the circulatory system. Objective: To investigate the role of psychological factors in periodontitis, considering it as the outcome as well as the influence of the level of periodontitis severity, as the exposure factor on acute myocardial infarction. Methods: This investigation is a result of data from a previous case-control study that estimated the association between periodontitis and acute myocardial infarction and it was divided into two stages. At first, it was conducted two cross-sectional studies to assess the association between common mental disorders and periodontitis (study 1) and between stress and periodontitis (study 2) in 621 individuals. The application of a questionnaire was carried out to obtain socioeconomic, demographic, lifestyle and health-related information. The common mental disorder was assessed by the Self Reporting Questionnaire (SRQ-20) and stress, the Perceived Stress Scale. The diagnosis of periodontitis was conducted from complete periodontal examination using: clinical attachment level, probing depth and bleeding on probing. Prevalence ratios (PR) and confidence intervals at 95% (95%CI) were obtained by Poisson regression analysis. In the second stage, a case-control study estimated the effect of the levels of periodontitis severity on acute myocardial infarction (study 3), with 207 individuals in the case group treated in the emergency Hospitals Santa Izabel and Ana Nery in Salvador, Bahia, Brazil, diagnosed with first acute myocardial infarction event, and 407 in the control group, without a diagnosis of acute myocardial infarction. Two criteria were used to define the levels of periodontitis severity. Unconditional logistic regression analysis was used to investigate the association between the levels of periodontitis severity and acute myocardial infarction: odds ratio (OR) and 95%CI.Results: The findings were presented in articles. Article 1 - showed that the occurrence of periodontitis among those exposed to common mental disorders was approximately 50% higher than in those without this mental condition, even after adjustment for age, sex, family income, current smoking habit, alcohol beverage consumption and cardiovascular disease (RPadjusted = 1.54, 95% CI: [1.13 to 2.10]). Article 2 - the measurements have demonstrated a positive association between stress and periodontitis, regardless the definition of the outcome: probing depth ≥ 4 mm (RPadjusted = 1.28, 95%CI: [1.04 to 1.58]), clinical attachment level ≥ 5mm (RPadjusted= 1.15, 95%CI: [1.01 to 1.31]) and periodontitis (RPadjusted= 1.36, 95%CI: [1.01 to 1.83]), after adjustment for age, sex, schooling level, current smoking habit, pulmonary disease and body mass index.Article 3 - strong positive association was found between severe and moderate periodontitis (RPadjusted = 2.21 to 3.92, and 1.96 to 2.51, respectively) with acute myocardial infarction, with statistical significance (p ≤ 0.05) for both diagnostic criteria of periodontitis. Conclusions: positive association between psychological factors and periodontitis has been demonstrated, as well as the dose-response effect of levels of periodontitis severity on acute myocardial infarction.